Pengaruh Ekstrak Daun Binahong (Anredera Cordifolia (Tenore) Steen) Terhadap Volume Urin Dan Hambatan Pembentukan Batu Ginjal Pada Tikus Terinduksi Etilen Glikol - Helmi Arifin; Vivi Resviana; Elisma Elisma (Jurnal Farmasi Higea, 2014)
Research on the effect of binahong leaf extract (Anredera Cordifolia (Tenore) Steen) on urine volume and resistance kidney stone formation in rat induced by ethylene glycol has been done. It purposed to look up the ability of the binahong leaf extract to increase the urine  volume and kidney stones shed on rats white males. That kidney stone formation induced by 0,75% ethylene glycol and 2% ammonium chloride for 7 days. 25 white male rats were divided into 5 groups,  group I were given drinking water (negative control), group II in the induction for 7 days (positive control), group III, IV and V were induced dose groups and given the extract at a dose of 50 mg/kg BB, 150mg/kg BB and 450mg/kg BB. Extracts was given on day 8-28, 24-hour urine volume were collected on days 7, 14, 21 and 28 for calcium level was measured by atomic absorption spectrophotometer and oxalat levels with ultraviolet and visible spectrophotometer. Data were analyzed by two-way ANOVA followed by advenced Duncan test. The urine volume was not significantly influenced by treatment factors and the duration of administration (P>0.05), while the levels of calcium and oxalat significantly influenced by treatment factors and the long time of administration (P<0.05) based on these results it could be concluded that binahong leaf extract could increase the urine volume and kidney stones shed. The effective dose is the dose kidney stone shed 450mg/kgBB. So the higher the dose and the longer the time of administration of calcium and oxalate levels also increased in the urine volume of rat white males.